Kekuasaan Simbolik di Media Sosial: Stigma terhadap Kritikus Pemerintah - Fardiyan, Ahmad Rudy (Sosiologi: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2015)
Media newborn to give hope for the democratization of information, which means that there is hope of discourse domination free communication. But in practice, social media is also not free from the domination because of differences in ideology and social status of the participants in it. This study discusses the symbolic power that occurs in social media Twitter account owner Indonesian President Susilo Bambang Yudhoyono, through a series of tweets, he responded to criticism of political observers in the same social media. Using the method of Roland Barthes semiotic and symbolic power of the concept of Pierre Bourdieu, the results of this study show that the text of Twitter revealed the existence of Symbolic Power in the form of stigma to the opposition or non-executives who heavily criticized the governments policy.Keywords: Social media, symbolic power, stigma